Pharmacotherapeutic options for prediabetes. (2nd January 2021) - Rendell, Marc
ABSTRACT: Introduction: 'Prediabetes' is a condition of elevated glucose not attaining the established criteria for a diagnosis of diabetes. The United States Diabetes Prevention Program (DPP) began in 1996 and was the iconic study of prediabetes. In that study, after 3 years, the risk of reaching the numerical criteria of diabetes was reduced by 58% by intensive emphasis on diet and exercise whereas treatment with metformin achieved a lesser reduction of 31%. The DPP was widely heralded as suggesting that lifestyle change was superior to pharmacologic therapy in the prediabetes population. This conclusion may be overreaching in terms of the long-term results of that study. Areas covered: The author reviews the subsequent pharmacologic efforts to prevent diabetes in this population. He reviews the existing literature for pharmacologic treatment of prediabetes using Pubmed.gov using the keywords of prediabetes, impaired fasting glucose and impaired glucose tolerance. Expert opinion: Prediabetes is primarily related to being overweight. Obesity has health consequences going beyond glucose elevation. The approach to prediabetes should be primarily by pursuing weight loss with therapeutic agents such as GLP-1 receptor agonists and SGLT2 inhibitors.